The road less travelled: Autobiographical expressive writings of North-South migrants to Guanajuato, Mexico - Claudia Christina Chibici-Revneanu (Entreciencias: Diálogos en la Sociedad del Conocimiento)
This article parts from the assumption that some common notions about migration are “narrative” in nature - both half-fictions and socially constructed “realities”. It looks at a trend frequently neglected by hegemonic narratives of human movement, namely North-South migration. More specifically, it focuses on some migrants to the state of Guanajuato, Mexico and their writings produced during two intercultural expressive and autobiographical writing workshops. The study draws from an interdisciplinary methodology, including migration studies with a sociological, anthropological, economic and psychological outlook, expressive writing studies, and narrative analysis of texts created. The workshop writings revealed both an emergent sense of a “common humanity” among participant movers, and the significant complexity of individual migrant experiences. Many of the tales told indeed questioned common “migration narratives” like neat nation-state to nation-state movement and North-South divisions, thus opening spaces for re-imagining migration in its full human universality, diversity and complexity.